HCN Content Estimation in Different Sorghum Genotypes under Rainfed Conditions - Aslam, Hira; Shabbir, Ghulam; Ahmed, Farooq; Khan , Azra; Jabeen, Aqsa; Draz , Muhammad Umar; Sahar, Arooba; Khan, Yasmeen; Rizwan, Muhammad; Jamshed, Muhammad (Indus Journal of Bioscience Research, 2025)
Sorghum is most important fodder in dry land areas. It has ability to tolerate high temperature and grow under minimal soil moisture conditions but under drought stress, the HCN content in sorghum increases which is dangerous for animals when used as fodder. Keeping in mind a study was conducted to measure HCN content in different genotypes of sorghum. The research materials were consisted of fifty-six genotypes and three check varieties. The experiment was laid out in an augmented block design at University Research Farm Chakwal Road during kharif season 2018. Samples were collected thirty days after germination and total cyanide was measured by picrate paper method. Results revealed that concentration of HCN varies significantly from genotype to genotype in comparison with checks. Lowest HCN content was found in genotypes JS-263, I-4 and S-9901 that was 201, 209 and 213 (mg/100g) so these genotypes can be used safely for fodder purposes in rainfed areas. Overall these genotypes JS-263, PARC-SS-2, PARC-SU-2, I-5, I-4, Nilli bar, YSS-4, Fri-04, JS-07, YSS-15 and YSS-98 performed good for all studied morphological traits. Significant negative correlation of HCN was observed with sugar content which shows that genotypes with high sugar content will have least HCN content. The results show significant variation among genotypes. JS-263, FM-147, PARC-SU-2, PARC-SS-2, and Nillibar performed well and can be used as fodder. Genetic parameters confirm potential for improving fodder yield. This study highlights genetic variability, indicating strong potential for trait improvement in sorghum breeding programs.